Four novels on the theory of economic growth - KOUMPAROULIS, Dimitrios Nikolaou (Journal of Economics Library, 2018)
Abstract. The aim of these notes is to assist the students of the Business Administration Department of the University of People, U.S.A. to understand critically some major aspects of the theory of economic growth. Keywords. Economic growth, Economic models, Quantitative economic applications. JEL. E10, E11, E13, E14, E19.